Lick the Toad: a web-based interface for collective sonification - Vasilakos, Konstantinos (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2021: Anais do XVIII Simpósio Brasileiro de Computação Musical, 2021)
Lick the Toad is an ongoing project developed as a web based interface that runs in modern browsers. It provides a custom made platform to collect user data accessed from mobile devices, such as smartphones, tablets etc. The system offers a tool for interactive collective sonification aiding the idea of networked music performance. It can be used in various contexts, such as onsite installation, interactive compositional tool, or for the distribution of raw data for live coding performances. The system embeds neural network capabilities for prediction purposes by using user input and outputs/targets alike. The inputs and the targets of the training processes can be adapted according to the needs of the use making it a versatile component for creative practice. It is developed as open-source project and it works currently as a NodeJS application with plans for future deployment on remote server to support remote communication and interaction amongst distant users.